Media, movements, and political change - Earl, Jennifer, 1974-; Rohlinger, Deana A. (Bingley, U.K. : Emerald, 2012)
This volume of Research in Social Movements, Conflicts and Change explores the relationships between mass media, social movements, and political change. Since Martin Luther nailed his Theses of Contention on the Wittenberg Church door in 1517, scholars and pundits have noted that the media plays an important role in social and political change. This volume advances scholarly understanding of how activists and elites alike use books, newspapers, and Internet-enabled technologies to affect change. Chapters include analyses of the role of media in the (Anti-)Abortion, Globalization, Labor, Townsend, and White Power movements as well as Barack Obamas 2008 campaign. Altogether, this volume suggests new avenues for research, provides new insights into the strategic use and influence of media, and challenges existing assumptions of media-movement relationships.
Introduction / Jennifer Earl, Deana A. Rohlinger -- Literary activists and battling books : the labor problem novel as contentious movement medium / Larry W. Isaac -- Outside the mainstream : social movement organization media coverage in mainstream and partisan news outlets / Deana A. Rohlinger, Ben Kail, Miles Taylor, Sarrah Conn -- A story-centered approach to the newspaper coverage of high-profile SMOs / Edwin Amenta, Beth Gharrity Gardner, Amber Celina Tierney, Anaid Yerena, Thomas Alan Elliott -- Media framing of the Pittsburgh G-20 protests / Rachel V. Kutz-Flamenbaum, Suzanne Staggenborg, Brittany J. Duncan -- Organizational dominance and its consequences in the online abortion rights and antiabortion movements / Katrina Kimport -- A social movement online community : Stormfront and the white nationalist movement / Neal Caren, Kay Jowers, Sarah Gaby -- Acting in the public sphere : the 2008 Obama campaign's strategic use of new media to shape narratives of the presidential race / Daniel Kreiss -- Mobilizing in response to threat : the case of the ex-gay movement / Jason Lee Crockett, Melinda D. Kane.
Keywords: Political Science -- Political Process -- General; Social Science -- Sociology -- General; Politics & government; Political campaigning & advertising; Social movements; Mass media -- Political aspects; Communication in social action